A missing link in the history of historiography: scholarly personae in the world of Alfred Dove. Issue 7 (3rd October 2019) - Paul, Herman
ABSTRACT: Drawing on the case of Alfred Dove (1844–1916), this article contributes to an emerging line of research on scholarly personae in the history of historiography. It does so by addressing the important but so far neglected question: What exactly does the prism of scholarly personae add to existing historiographical perspectives? The German historian Alfred Dove is an appropriate case study for this exercise, because historical scholarship in Wilhelmine Germany has been relatively well studied, from various angles. Most notably, it has been studied (1) through biographical lenses, (2) from institutional points of view, (3) as the cradle of 'scientific history', with special attention to historical methods of the sort codified by Ernst Bernheim, and (4) in relation to religious and political fault lines that divided the German Empire shortly after the Franco-Prussian War and the Kulturkampf . The thesis advanced in this article is that scholarly personae are a missing link between these four dimensions and therefore a theme of key importance for anyone trying to understand German historical studies in the late nineteenth and early twentieth centuries.